Ex vivo near-infrared targeted imaging of human bladder carcinoma by ICG-anti-CD47 - Hao, Haifeng; Wang, Xinyu; Qin, Yan; Ma, Zhifang; Yan, Pengyu; Liu, Chao; Chen, Guanying; Yang, Xiaofeng (Frontiers in Oncology, 2023)
Objective: The low detection rate of early-stage and small tumors remains a clinical challenge. A solution to this unmet need is urgently warranted for the accurate diagnosis and treatment of bladder cancer (BC). This study aimed to evaluate the feasibility of CD47 as a target for optical molecular imaging of human BC and conduct preliminary ex vivo imaging experiments. Method: Using indocyanine green (ICG) and a CD47 antibody (anti-CD47), we synthesized a new targeted fluorescent probe ICG-anti-CD47. A total of 25 patients undergoing radical cystectomy were prospectively included in ex vivo imaging experiments. Following surgery, the freshly isolated bladder specimens were incubated with ICG-anti-CD47, and images were captured under white light and near-infrared (NIR) light. Standard histopathologic evaluation was performed, and findings were correlated with those of CD47-targeted NIR molecular imaging. Results: Based on the ex vivo imaging experiments, 23 and 2 patients were pathologically diagnosed with bladder urothelial carcinoma and bladder squamous cell carcinoma, respectively. There were no adverse effects of ICG-anti-CD47 on the histological structure of the tumor and normal uroepithelium. In the NIR grayscale images, the mean fluorescence intensity of the tumor tissue was significantly higher than that of the adjacent normal background tissue, which markedly improved tumor visualization. Conclusion: Anti-CD47-targeted NIR molecular imaging may be a feasible and powerful strategy for the accurate diagnosis of BC. Nevertheless, larger-scale randomized trials are warranted to verify the present findings.